Risk regulation in the internal market : lessons from agricultural biotechnology - Weimer, Maria (Oxford : Oxford University Press, 2019)
This book is a topical inquiry into the limits of EU integration in the field of risk and new technologies surrounded by techno-scientific complexity, uncertainty, and societal contestation. It uses agricultural biotechnology to illustrate the intertwinement between environmental, public health, economic and social concerns in risk regulation.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 7, 2019).
Keywords: Agricultural biotechnology -- Law and legislation -- European Union countries; Genetically modified foods -- Law and legislation -- European Union countries; Risk management -- European Union countries